Building social capital to counter polarization and extremism? A comparative analysis of tech platforms' official blog posts - Maura Conway (First Monday, 2022)
This research employs the concept of social capital to compare the efforts that a range of tech companies have claimed to take to counter polarization and extremism and build resilience on their platforms. The dataset on which our analysis is based is made-up of a purposive sample of official blog posts from three ‘older’ (i.e., Facebook, Twitter, YouTube) and three ‘newer’ (i.e., TikTok, Discord, and Telegram) technology platforms. The selected posts focused on companies’ efforts to make their platform safer, build community resilience, counter violent extremism and/or polarization, or mentioned related topics such as countering hate organizations, radicalization, or misinformation. Revealed were seven themes incorporating, to a greater or lesser extent, the three main types of social capital (i.e., bonding, bridging and linking). These themes were granting user powers, strengthening existing communities, provision of information and education, building community, enhancing user rights, keeping users safe, and building trust and relationships with users. Analysis of these showed that while creation of all three types of social capital was apparent, similar to previous studies, bridging capital dominated here too; while there were some discrepancies between social capital generating activities and their framings on ‘older’ versus ‘newer’ platforms, other factors, including platform size and company values are likely to be equally or more important; and, finally, that companies attempts at generating online social capital can have negative as well as positive impacts with regard to countering polarization and extremism.